The Use of Total Physical Response (TPR) Activities for Teaching Listening to Young Learners - Inti Englishtina (Journal of English Language Teaching and Islamic Integration, 2019)
Although  infants  are  not  speaking,  they  are  still  active  users  of  the language because they are physically responding to what has been said. As teachers of second and foreign-language learners, it is useful to consider the listening skills that  are  taught  to  children  learning  English  as  a  first  language.  This  article examines the use of Total Physical Response (TPR) activity as one of the activities for  teaching  listening  to  young  learners.  The  article  begins  with  the  concept  of Total Physical Response (TPR) activity, and continues with various ways of using this activity for teaching listening to young learners. In addition, the effectiveness of this activity is also discussed.